Numerical Simulation on the Diffusion of Alien Phytoplankton in Bohai Bay - Zhang, Beibei; Pu, Amin; Jia, Peng; Xu, Chenglong; Wang, Qinggai; Tang, Wenhao (Frontiers in Ecology and Evolution, 2021)
In order to investigate the motion feature of alien phytoplankton in the Bohai Bay area, this paper combines the biological characteristics of phytoplankton in the Bohai Bay to build a two-dimensional tide hydrodynamic and particle tracking coupling model to simulate the phytoplankton at different specific growth rates. The characteristics of the movement trajectory of the three major ports in the Bohai Bay (Caofeidian Port, Tianjin Port, and Huanghua Port) and the diffusion processes. The results show that the movement of alien phytoplankton is mainly affected by the tidal circulation near the port. The diffusion trend is basically consistent with the residual flow field in the Bohai Bay, and its distribution density is directly affected by the specific growth rate of the population and is positively related to the specific growth rate; the release of alien phytoplankton at the three major ports is all concentrated around the ports, with the largest distribution density in Tianjin Port, and the possibility of red tide disasters is also greatest compared to the other two major ports; it is necessary to strengthen the monitoring of alien organisms in the port area and actively prevent alien phytoplankton from entering Bohai Bay through ship ballast water.